POTENSI KEMBANG SUSUT TANAH EKSPANSIF DI WILAYAH SOLO RAYA (Studi Kasus di Trucuk, Pedan, dan Nogosari) - Siti Nurlita Fitri; Niken Silmi Surjandari; Noegroho Djarwanti; Yusep Muslih Purwana; Bambang Setiawan; Harya Dananjaya; Brilian Budi Prakosa (Matriks Teknik Sipil, 2021)
Expansive soil has commonly found in several areas around infrastructure projects such as; highways, irrigation systems, buildings, and bridges. The behavior of expansive soils affects the strengths and durability of the upper structure. The main characteristic of expansive soil is the swell-shrinkage influenced by water content. Moreover, the negative trait harms the structure. For example,  the cracks of the highway pavement and building wall and differential settlements in bridges abutment are the damage phenomena caused by expansive soil. The soil spread in several area near Surakarta residency namely Nogosari, Boyolali , Cawas Pedan, Klaten Regency, Bendosari Gentan, Sukoharjo and Purwodadi. Therefore, these areas have high vulnerability damage of Expansive soil. The study for determining and collecting data on the potential for shrinkage, which is a characteristic of expansive soil, is necessary conduct. This research aims to identify the swell-shrinkage potential in laboratory tests. The test had carried out with property index(water content and Atterberg limit) following code standards (SNI and ASTM). The liquid limit values for the Trucuk, Padan, and Nogosari areas are 84.75%, respectively; 73.56% and 49.05%. The plasticity index values for the Trucuk, Padan, and Nogosari regions are as follows: 66.97%; 45.72%; and 28.74%. Activity (AC) values for the 3 Pedan, Trucuk, and Nogosari locations are as follows: 1.61; 1.67; and 1.28. The value results are based on laboratory tests output, were 3 locations in the Klaten area, namely Trucuk, Pedan, and Nogosari. In summary, the zones have high susceptibility area damage by expansive soil. The result of this study is expected to be preliminary mapping guidance surround the Surakarta Residency